A High-Content Screening Approach to Identify MicroRNAs Against Head and Neck Cancer Cell Survival and EMT in an Inflammatory Microenvironment - Sangiorgi, Bruno; de Souza, Felipe Canto; Mota de Souza Lima, Ildercílio; dos Santos Schiavinato, Josiane Lilian; Corveloni, Amanda Cristina; Thomé, Carolina Hassibe; Araújo Silva, Wilson; Faça, Vitor Marcel; Covas, Dimas Tadeu; Zago, Marco Antônio; Panepucci, Rodrigo Alexandre (Frontiers in Oncology, 2019)
Head and neck squamous cell carcinoma (HNSCC) is among the most common cancer types. Metastasis, the main cause of death by cancer, can be promoted by an inflammatory microenvironment, which induces epithelial-mesenchymal transition (EMT) through a NF-kB-mediated stabilization of Snail. Here, we aimed to explore how microRNAs (miRs) can affect cell survival and EMT in HNSCC cells under an inflammatory microenvironment. By using an high-content screening (HCS) approach, we evaluated alterations in morphometric parameters, as well as expression/localization of Snail/Slug, in HNSCC cells primed with TNF-α. Based on those quantitation, we established the optimal experimental conditions of EMT induction driven by TNF-α. Those conditions were applied to cells transfected with distinct miRs (N = 31), followed by clusterization of miRs based on alterations related to cell survival and EMT. The signaling pathways enriched with molecular targets from each group of miRs were identified by in silico analyses. Finally, cells were transfected with siRNAs against signaling pathways targeted by miRs with anti-survival/EMT effect and evaluated for alterations in cell survival and EMT. Overall, we observed that TNF-α, at 20 ng/ml, induced EMT-related changes in cell morphology, Snail/Slug expression and cell migration. Predicted targets of miRs with anti-survival/EMT effect were enriched with targets of NF-kB, PI3K/ATK and Wnt/beta catenin pathways. Strikingly, individual gene silencing of elements from those pathways, namely RELA (NF-kB), AKT1 (PI3K/AKT) and CTNNB1 (Wnt/beta catenin) reduced cell survival and/or expression of Snail/Slug in cells stimulated with TNF-α. As a whole, our HCS approach allowed for the identification of miRs capable of inhibiting cell survival and EMT considering the presence of an inflammatory microenvironment, also indicating the common signaling pathways and molecular targets most likely to underlie those alterations. These findings may contribute to the development of targeted therapies against HNSCC.